2011
DOI: 10.2225/vol14-issue4-fulltext-1
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic biodegradation of nonylphenol ethoxylates in shaking-flask test

Abstract: Nonylphenol ethoxylates (NPEOs), which are widely used for industrial and domestic purposes, exert adverse effects on wildlife after being used and discharged into the environment. However, their ultimate biodegradability and biodegradation pathway remains unclear. In this study, the aerobic degradability of nonylphenol ethoxylates (NPEOs) by the acclimated microorganisms in active sludge was examined using shaking-flask tests. The degradation of benzene rings in NPEOs was determined using UV spectroscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…NPEO x and its derivative degrading bacterial strains have been isolated from several natural environments and wastewater treatment plants [1, 5, 21, 30, 5759]. In this paper the reported data indicated that indigenous bacterial strains, isolated from soil, are able to use NPEO 15 as the sole carbon source.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…NPEO x and its derivative degrading bacterial strains have been isolated from several natural environments and wastewater treatment plants [1, 5, 21, 30, 5759]. In this paper the reported data indicated that indigenous bacterial strains, isolated from soil, are able to use NPEO 15 as the sole carbon source.…”
Section: Resultsmentioning
confidence: 91%
“…The degradation of the aromatic ring occurs under aerobic conditions yielding several soluble metabolites which are finally degraded to CO 2 [30]; the kinetic order of the reaction corresponds to a first-order process [31, 32]. In anaerobiosis, Pseudomonas putida degraded NPEO x , with different length chains ( x = 6, 9 and 20), yielding as a final product NPEO 2 , no carboxylic acids were detected [8].…”
Section: Introductionmentioning
confidence: 99%
“…The nonionic surfactant was determined by spectrophotometric analysis with phosphomolybdic acid [28]. The degradation of the aromatic ring of neonol AF9-12 and isononylphenol was determined spectrophotometrically at 277 nm [29].…”
Section: Spectrophotometric Analysismentioning
confidence: 99%
“…In our experiments metabolites on sorghum germination, lengt (Figure 6). Control levels represent the corre of shoots, length of roots) in control treatme The use of spectrophotometric methods [28,29] revealed that basidiomycetes P. ostreatus f. Florida, P. ostreatus MUT, P. ostreatus 336, P. ostreatus LE-BINB, B. adusta, S. commune, and ascomycete C. herbarum attacked the oxyethyl chain, while the aromatic ring remained intact. S. rugosoannulata and T. ochracea degraded the aromatic ring.…”
Section: The Study Of the Phytotoxicity Of Parent Comentioning
confidence: 99%
“…PH was adjusted to 7 with buffer solution. All inoculated plates were incubated at 30°C for 5-7 days [24] .Control was prepared simultaneously without carbon source. Three parallel tests for NPEOs and control plates were carried out.…”
Section: Primary Screening Of Fungal Isolates Capable Of Degrading No...mentioning
confidence: 99%